Creating the Application of Green Architecture Principles in Hotel Buildings in Yogyakarta - Siddiq, Vieka Alana Leyla; Santonio, Sanchia Caroline; Pudianti, Anna; Sumardiyanto, B. (Journal of Architectural Research and Education, 2026)
Yogyakarta is a city that generates revenue, particularly from the tourism sector. The tourism sector requires accommodation in the form of lodging. This study discusses the application of green architecture principles in hotel buildings in Yogyakarta, specifically in Sleman Regency. Sleman Regency is the area experiencing the fastest urban development due to its location near the Keraton (the center of power). The study focuses on the green architecture principles applied in 3-star, 4-star, and 5-star hotels, including conserving energy, working with climate, respect for site, respect for user, limiting new resources, and holistic approaches. The objective of this study is to determine whether the implementation of green architecture principles affects the star ratings of hotels. The research uses a qualitative approach, referring to a comparative method of analyzing the application of green architecture principles in star-rated hotels. Comparisons are based on literature sources, and the analysis is directly illustrated through diagrams and visuals. The results include comparisons of star-rated hotel buildings that implement green architecture principles. The conclusion identifies the hotel with the most green architecture principles, making it more attractive to visitors. It alsoprovides recommendations to address deficiencies in the application of these principles for future improvements.